Cybersecurity Law Exploration: Personal Data Protection in 2023 - Reformasi, Titis Pandan Wangi; Buamona, Hasrul (Journal of Legal and Cultural Analytics, 2024)
In the ever-evolving digital era, an in-depth exploration of the cybersecurity legal framework is a must. This article examines the background and discussion of personal data protection in 2023. It provides a comprehensive overview of the current cybersecurity landscape, identifying key trends and threats faced by individuals, businesses, and governments. The focus then shifts to regulatory and compliance analysis, exploring potential changes and evaluating the adequacy of current regulations. Next, we outline the latest technologies used in data protection, detailing the role of artificial intelligence (AI) to blockchain in strengthening cybersecurity. Ethical aspects are also highlighted, exploring how efforts to improve security can be balanced with individuals’ right to privacy and preventing abuse of power by authorities. Through analysis of key cases in 2023, this article highlights real-world experiences related to personal data breaches. From here, readers can gain a deeper understanding of how cybersecurity law is evolving and addressing the ever-growing threats in this digital era. This article aims to provide a holistic view, educating readers about the current challenges and innovations in personal data protection and contributing to a deeper understanding of the field.